Prevalence of Self-medication of Antibiotics among People in Bangladesh - C, Nishat; M.I, Rashedul; H. MD, Mehedi; M., Rouf Md. (Indian Journal of Pharmacy Practice)
This study attempts to investigate the prevalence of self-medication of antibiotics among people in Bangladesh.This study was conducted in six districts of Bangladesh (Dhaka, Munshiganj, Kishoreganj, Chittagong, Chandpur, Kushtia) by collecting data on antimicrobial medication purchasing from retail drug stores established at the major streets. 750 customers were surveyed within the month of July 2009. The selfmedication rates for ciprofloxacin, doxycycline, ampicillin, amoxicillin, azithromycin, cefradine and metronidazole were 3.6% (n=27), 5% (n=39), 1% (8), 2% (15), 1% (9), 1% (10) and 9% (68) respectively. The self medication rates for erythromycin, flucloxacillin, tetracycline, cefixime, cefpodoxime, cefuroxime and cotrimoxazole were less than one percent. The misuse incidences are self medicating with ciprofloxacin to treat menstrual irregularity and abdominal pain, metronidazole to treat fever and menstrual irregularity, amoxicillin to treat viral diseases, ampicillin to treat scabies, azithromycin to treat pain etc. We recommend immediate establishment of community pharmacies run by qualified pharmacists who would spend more time for patients and prescription only status of antimicrobials in Bangladesh.
Keywords: Antimicrobials; Bangladesh; Self-medication; Resistance; Misuse